Why Does the “Sinner” Act Prosocially? The Mediating Role of Guilt and the Moderating Role of Moral Identity in Motivating Moral Cleansing - Ding, Wan; Xie, Ruibo; Sun, Binghai; Li, Weijian; Wang, Duo; Zhen, Rui (Frontiers in Psychology, 2016)
Numerous studies have found that people tend to commit prosocial acts subsequent to previous immoral acts, as a response to the latter. This phenomenon is called moral cleansing or moral compensation. However, the specific mechanism how previous immoral acts motivate moral compensatory behaviors is still not fully understood. This study aimed to examine the roles of guilt and moral identity in the relation between previous immoral acts and subsequent prosocial behaviors to clarify the mechanism. Based on the extant research, the current study proposed a moderated mediation model to illustrate the process of moral cleansing. Specifically, a previous immoral act motivates guilt, which further leads to subsequent prosocial behaviors, while moral identity facilitates this process. The participants were primed by a recalling task (immoral act vs. a neutral event). The results support the hypothesized model and provide a framework that explains moral cleansing by integrating the roles of guilt and moral identity. These findings highlight the dynamic nature of people’s morality with regard to how people adapt moral behaviors to protect their moral self-image.